Dietary sodium intake and all-cause mortality in rheumatoid arthritis: an NHANES analysis (2003–2018) - Dongyi Li; Jiajun Li; Yiming Li; Ying Guan (Frontiers in Nutrition)
BackgroundIn the field of nutritional epidemiology, the association between sodium intake and all-cause mortality in patients with rheumatoid arthritis (RA) remains inadequately explored. Consequently, the impact of sodium consumption on the prognosis of RA patients is not clearly defined, which leaves clinicians without adequate data to guide dietary sodium recommendations.ObjectivesThis study seeks to examine the potential relationship between sodium intake in the diets of patients with RA and all-cause mortality.MethodsA prospective cohort study analyzed 2,856 patients aged 20 and older with RA who participated in the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2018. Comprehensive data on mortality, dietary sodium intake, and relevant confounding variables were systematically collected. Cox regression and restricted Cubic Splines (RCS) were employed to explore the potential associations.ResultsAfter adjusting for confounding factors, a significant inverse correlation was observed between dietary sodium intake and the risk of all-cause mortality in patients with RA. When sodium intake was treated as a continuous variable, the hazard ratio (HR) was 0.68 (95% CI: 0.56–0.81, p < 0.001). When sodium intake was categorized into quartiles, compared to the lowest intake group Q1 (≤ 2.1 g/day), the HRs for Q2, Q3, and Q4 (2.1–2.8 g/day, 2.8–3.7 g/day, and ≥ 3.7 g/day) were 0.89 (95% CI: 0.75–1.06, p = 0.212), 0.74 (95% CI: 0.62–0.88, p = 0.001), and 0.70 (95% CI: 0.58–0.85, p < 0.001), respectively. The nonlinear model revealed a threshold effect, identifying a breakpoint at a sodium intake of 3.1 g/day. Below this threshold, for each additional unit of intake, the risk of all-cause mortality decreased by 14% (HR = 0.86).ConclusionThe findings of this study demonstrate a negative correlation between increased dietary sodium intake and all-cause mortality risk in patients with RA within a specific range. The threshold analysis identified a breakpoint at a sodium intake of 3.1 g per day, which is equivalent to approximately 7.9 grams of salt, exceeding the World Health Organization (WHO) recommendation of 5 grams of salt per day. These findings challenge the prevailing notion that higher sodium intake is always detrimental. This may offer valuable insights for developing dietary guidelines for RA patients.